Vascular Age, Metabolic Panel, Cardiovascular Risk and Inflammaging in Patients With Rheumatoid Arthritis Compared With Patients With Osteoarthritis - Rodríguez-Vargas, Gabriel-Santiago; Santos-Moreno, Pedro; Rubio-Rubio, Jaime-Andrés; Bautista-Niño, Paula-Katherine; Echeverri, Darío; Gutiérrez-Castañeda, Luz-Dary; Sierra-Matamoros, Fabio; Navarrete, Stephania; Aparicio, Anggie; Saenz, Luis; Rojas-Villarraga, Adriana (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The risk of cardiovascular disease (CVD) in patients with rheumatoid arthritis (RA) is 1.5-2 times higher than the general population. The fundamental risk factor for CVD is age, related to alterations at the arterial level called vascular aging. The aim of the study was to compare vascular age (VA) in RA patients under a strict treat-to-target (T2T) strategy with Osteoarthritis (OA) patients without strict follow up and to assess the influence of inflammaging (chronic, sterile, low-grade inflammation related with ageing) and metabolic markers on VA. Materials and methods: This was an analytical cross-sectional study. Patients with RA (under a strict a T2T strategy) and OA patients without strict clinical follow-up, were included. Patients with history of uncontrolled hypertension, CVD and/or current smoking were excluded. Sociodemographic, physical activity and toxic exposure data, were obtained. Waist-hip ratio and body mass index (BMI) were measured. DAS-28 (RA) and inflammatory markers, lipid profile and glycaemia were analyzed. Pulse wave velocity (PWV) was measured (oscillometric method, Arteriograph-TensioMed®). VA was calculated based on PWV. Eleven components of the inflammaging were evaluated (Luminex® system). Univariate and bivariate analyzes (Mann Whitney U and chi-square) and correlations (Spearmans Rho) were performed to compare the two groups. Results: A total of 106 patients (74% women) were included, 52/RA and 54/OA. The mean age was 57 (Interquartile range - IQR 9 years). The BMI, waist circumference and weight were higher in patients with OA (p <0.001). RA patients had low disease activity (DAS-28-CRP). There were no differences in VA, inflammaging nor in PWV between the two groups. VA had a positive, but weak correlation, with age and LDL. In group of RA, VA was higher in those who did not receive methotrexate (p = 0.013). LDL levels correlated with MMP1, TIMP1, and TIMP2. Conclusions: When comparing RA patients with low levels of disease activity with OA patients with poor metabolic control, there are no differences on VA. Furthermore, methotrexate also influences VA in RA patients. This shows that implemented therapies may have an impact on not only the inflammatory state of the joint but also CVD risk.